SeHCAT [tauroselcholic (selenium-75) acid] for the investigation of bile acid malabsorption and measurement of bile acid pool loss : a systematic review and cost-effectiveness analysis /: a systematic review and cost-effectiveness analysis. (December 2013) - Riemsma, R. P
No abstract available